2009
DOI: 10.1253/circj.cj-08-0141
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Peripheral Artery Disease Who Complete 12-Week Supervised Exercise Training Program Show Reduced Cardiovascular Mortality and Morbidity

Abstract: Supervised exercise training improved cardiovascular mortality and morbidity in patients with PAD, which suggests that exercise training should be considered as a secondary prevention strategy for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 46 publications
1
55
0
1
Order By: Relevance
“…31 In addition, supervised exercise training improved cardiovascular mortality and morbidity in patients with PVD, which suggests that exercise training should be considered as a secondary prevention strategy for these patients. 32 The authors, however, did not analyze the differences of technical and/or clinical outcomes vs. presence of medication and/or rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, supervised exercise training improved cardiovascular mortality and morbidity in patients with PVD, which suggests that exercise training should be considered as a secondary prevention strategy for these patients. 32 The authors, however, did not analyze the differences of technical and/or clinical outcomes vs. presence of medication and/or rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%
“…7 The changes made by a large number of these patients could have an impact on the mortality and morbidity of these people. 8 This reinforces the importance of the role of healthcare professionals who care for patients with long-term conditions which could predispose them to arterial disease to recognise it early, and refer on for further investigation and management of their cardiovascular risk factors. The outcomes also tie in with the UK Healthy Cities Network.…”
Section: Discussionmentioning
confidence: 73%
“…One study compared the long-term outcomes of PAD patients who engaged with a structured exercise programme with support to address modifiable cardiovascular risk factors with outcomes for PAD patients who did not. 8 Over a 13-year period it found that overall cardiovascular mortality was reduced by 52% and morbidity by 30%. The patients who engaged with the programme were largely empowered to take more ownership of their health, and this can only be a positive outcome.…”
Section: Key Messagesmentioning
confidence: 99%
“…Furthermore, a current study declared that prostaglandin E1 in lipid microspheres enhanced walking ability and Life quality as self-estimated by PAOD patients [47]. Besides, supervised training exercise enhanced cardiovascular mortality and morbidity in PAOD patients, which recommends that training exercise, could be deemed as a secondary prevention policy for those subjects [48].…”
Section: Discussionmentioning
confidence: 85%